Critical care management of acute ischemic stroke – An overview of current concepts - Sengupta, Deep; Mahajan, Charu; Kapoor, Indu; Prabhakar, Hemanshu (Journal of Nepalese Society of Critical Care Medicine, 2024)
Acute ischemic stroke is a major cause of morbidity and mortality globally. Early recognition and prompt revascularisation are the cornerstones of treatment. Advances in the management of stroke, notably with the endovascular interventions has led to improved functional outcomes. Identification of stroke subtype, timely decision making, institution of specific therapy and periprocedural care in an intensive care unit make the difference between a favourable and an unfavourable outcome. To this effect, dedicated stroke centres, multidisciplinary teams with trained experts and critical care management play an important role. Improvements in the understanding of the disease process, ever expanding literature and development of promising novel therapeutic strategies, not withstanding, stroke is still a leading cause of acquired long term disability and mortality worldwide. End of life care and associated decision making precariousness, pose a significant prognostication challenge to the critical care team. The aim of this review is to discuss the current evidence regarding diagnosis, revascularisation modalities and optimal critical care management strategies.